Cybercrime 2.0: When the Cloud Turns Dark. - Provos, Niels; Rajab, Moheeb Abu; Mavrommatis, Panayiotis (Communications of the ACM, 2009)
The article discusses efforts to prevent Web-based malware attacks, describing Web attack trends and examining the open challenges associated with the threat of such cybercrime. Today's adversaries are primarily motivated by economic incentives to exploit and seize control of compromised systems for as long as possible, the authors state, turning seized assets into revenue. Other topics include the monetizing of compromised computer systems, running arbitrary code on compromised users' computers, and vulnerabilities that come with complex software.